Using preschoolers to improve caregivers' knowledge, attitude, and practices relating to biofortified crops: Evidence from a randomized nutrition education trial in Kenya - Ojwang, S.O.; Okello, J.J.; Otieno, David Jakinda; Nyikal, R.A.; Muoki, Penina Ngusye (Wiley, 2022)
This 2018 randomized controlled trial examined the role behavioral nudges can play in improving caregivers' knowledge, attitude, and practices (KAP) relating to biofortified orange-fleshed sweetpotato (OFSP). The experiment involved 431 preschooler– caregiver pairs in 15 villages. The preschoolers were enrolled in public-run Early Childhood Development and Education (ECDE) centers in the respective villages. Caregivers were first exposed to the routine OFSP promotion activities in the area – invited to cooking demonstration workshops and issued with free OFSP vines to plant. A baseline survey followed. Next, the 15 villages were randomized into four study groups (a control and three treatments). The interventions were deployed for 30 days as follows: Treatment 1 – preschoolers issued OFSP-branded exercise books, class posters, and poems; Treatment 2 – caregivers received phone-mediated text messages; and Treatment 3 – received the full suite of interventions. This study analyzed the endline and baseline data and finds that, in general, changes in KAP scores were negatively associated with control group (p = .005) and positively associated with Treatment 3 (p = .02). Specifically, Treatment 3 significantly increased caregivers' knowledge of OFSP production, consumption, and vitamin A. Treatment 2 significantly improved their attitude too. It concludes that an integrated complementary nutrition education approach targeting preschooler–caregiver pairs is more effective in increasing knowledge of cultivation and consumption of OFSP. It discusses the implications for the design of more effective nutrition programs targeting households with preschoolers to accelerate the fight against vitamin A deficiency (VAD).